Penerapan Pengendalian Persediaan Material Dinamit/Expogel Menggunakan Metode Inventori Probabilistik Model Q-Back Order di PT Pindad (Persero) - Ifa Saidatuningtyas; Muhammad Alde Rizal; Dhea Tisane Ardhan; Sri Rahayu (Politeknik ATI Padang, 2022)
PT Pindad (Persero) is in charge of producing commercial military products for the benefit of the government and private sector. However, in its production activities, the company has difficulties in controlling the inventory, one of which is in the dynamite/expo gel component. Stock control using probabilistic inventory method Q-back order model is used to balance between the needs of goods that must be provided and maintain the decrease in sales due to the shortage of goods. This study aims to determine the size of the order lot that minimizes the cost of supplies on the dynamite/expo gel component at PT Pindad (Persero). The optimal order lot size of the calculation result was with service level of 97.77%. The comparison with company policy showed a decrease in total inventory cost of 0.6% and a decrease in storage costs of 88%.